2, 6-Bis(5, 6-diisopropyl-1, 2, 4-triazin-3-yl)pyridine: a highly selective N-donor ligand studied by TRLFS, liquid–liquid extraction and molecular dynamics. (14th November 2016) - Beele, Björn B.; Skerencak-Frech, Andrej; Stein, Arnulf; Trumm, Michael; Wilden, Andreas; Lange, Steve; Modolo, Giuseppe; Müllich, Udo; Schimmelpfennig, Bernd; Geist, Andreas; Panak, Petra J.
Abstract : Studying the effect of modifications of BTP-ligands on the complexation and separation of Ln(iii ) and An(iii ). Abstract : The complexation of Cm(iii ) and Eu(iii ) with 2, 6-bis(5, 6-di-i-propyl-1, 2, 4-triazin-3-yl)-pyridine ( i Pr-BTP) is studied in methanol : water (1 : 1, vol) by time-resolved laser-induced fluorescence spectroscopy (TRLFS). With increasing ligand concentration [Cm( i Pr-BTP)3 ] 3+ and [Eu( i Pr-BTP)3 ] 3+ are formed, respectively. Stability constants of log β 3 ′([Cm( i Pr-BTP)3 ] 3+ ) = 16.3 ± 0.3 and log β 3 ′([Eu( i Pr-BTP)3 ] 3+ ) = 14.9 ± 0.3 are determined. Thermodynamic data of the complexation reactions is obtained in a temperature range of 20–60 °C. The complexation of i Pr-BTP with both metal ions is exothermic (Cm(iii ): Δr H 3 ′ = −(64.1 ± 3.0) kJ mol −1 ; Eu(iii ): Δr H 3 ′ = −(42.6 ± 2.0) kJ mol −1 ). The reaction entropy for the formation of [Eu( i Pr-BTP)3 ] 3+ is higher compared to the Cm(iii ) complex (Cm(iii ): Δr S 3 ′ = (96.5 ± 6.5) J mol −1 K −1 ; Eu(iii ): Δr S 3 ′ = (136.0 ± 15.2) J mol −1 K −1 ). Different complexation entropies for the formation of [Cm( i Pr-BTP)3 ] and [Cm( n Pr-BTP)3 ] are explained by molecular dynamics simulations. Results from liquid–liquid extraction tests confirm the ligand's peculiar extraction kinetics observed in previous studies and link them to the thermodynamic data.